Pengaruh Inovasi Layanan Electronic Banking, Fee Based Income dan Efektivitas Pengendalian Internal terhadap Nilai Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia - Miranda Nuraini; Tafdil Husni; Fajri Adrianto (Universitas Batanghari, 2022)
The banking industry must also continue to innovate in the development of electronic banking products and services to keep up with the rapid development of information technology, which has an impact on people's habits and routines. To further reduce the need for customers to physically visit a bank branch, financial institutions must enhance their offerings to allow for the self-service acquisition of a wide range of banking services (including but not limited to account opening, account maintenance, account transfer, and account closure). The purpose of this research was to examine the impact of technological advancements in electronic banking services, fee-based income, and efficient internal control on the market value of IDX-listed banks in the sub-sector from 2016 to 2020. Sampled from the larger population of IDX-listed financial services firms over the years 2016-2020, this study focuses on the banking industry. The study's population consists of 44 IDX-listed financial services firms. There were a total of 185 observations made for this study. Descriptive research was used for this analysis. Intentional sampling. The study found that the probability value of the innovation of e-banking was 0.005. This is less than the 5% threshold (0.00500.05), so H1 is accepted. According to the results of the second hypothesis (H2) test, banking companies' stock prices rise when they bring in more money from service fees. The study found that a probability value of 0.003 at the FBI level was statistically significant. Compared to the 5% significance level of 0.0030.05, this value is less than the threshold for accepting hypothesis 2. The third hypothesis H3 tests the idea that the efficiency of internal control has a significant positive effect on the value of financial institutions. A probability value of 0.0057 0.05 was assigned to the efficiency of internal control based on the findings of the study. In other words, we accept H3 as true. The purpose of this research was to determine how the introduction of new forms of electronic banking, the growth of fee-based revenue, and the efficiency of internal control affect the market value of financial institutions.